Gender Study on the Profile of Postgraduate Innovation Candidates in Southern Tamaulipas - Soto Hernández, Ana María; Camero Berrones, Rosa Gabriela; Maldonado Soto, Otilia Georgina; Vargas Pérez, Laura Silvia; Reyes García, Brenda Lizeth; Reyes Méndez, Victoriano (LACCEI, 2025)
A study carried out with a sample of 74 undergraduate applicants on management in a technological institution in northern Mexico showed greater interest from women, reaching a parity index of 1.39, with 69.8% being engineers. Hypothesis tests indicate that there are no significant differences between men and women for age, career, labor sector, study modality. Nor for professional profiles such as: project management, intellectual property, social responsibility, entrepreneurship or education. However, the factorial analysis shows a clear difference in the integration of components for women and men. Women present two well-separated groups of elements: the previous profiles, and the virtual or mixed study modalities. In men, the following stand out: intellectual property, social responsibility and entrepreneurship; and there is no preference in study modalities.